0340 Differentially expressed miRNAs in skeletal muscle related to feed efficiency in Nellore cattle. (1st October 2016) - Oliveira, P. S. N.; Tizioto, P. C.; Oliveira, G. B.; Cesar, A. S. M.; Diniz, W. J. S.; Lima, A. O. D.; Reecy, J. M.; Coutinho, L. L.; Regitano, L. C. A.
Abstract: Feed efficiency (FE), also referred as residual feed intake (RFI), is a production trait that can have a major impact on production costs, reduction of pasture area, and pollutants. Bovine transcriptomic studies have shown that the expression of many miRNAs are tissue specific and have potential roles in some biological mechanisms. In this study, Nellore steers genetically divergent for RFI (kg/d) were selected based on BLUP (Best Linear Unbiased Prediction) estimates and ranked to select the most extreme values for additive genetic merit. Sequencing of small RNA libraries from Longissimus dorsi (LD) muscle tissue of eight Nellore steers ( N = 4 High RFI, N = 4 Low RFI) was conducted on a MiSeq using the Miseq Reagent Kit V3 150 cycles. After quality control, the miRDeep2 software was used to identify and quantify novel and known miRNAs using Bos taurus UMD3.1 as reference genome. Differentially expressed (DE) miRNAs (FDR = 10%) were identified by DESeq2 R package and potential regulatory target transcripts were predicted by TargetScan software. The bta-miR-486 (padj = 0.0072) was DE in LD muscle tissue. This miRNA was also identified as DE in a transcriptome analysis in skeletal muscle for differential RFI in pigs. The genes PKHD1L1, ENAH, ATF3, GAS7, LIMK1, MPZ, C3 and SLC26A2, related to ion transport, glucose and pyruvate metabolic process and glycosylation, were identified as target genes of this DE miRNA. Supporting our findings, these genes were previously identified as DE in RNaseq study performed using liver and muscle tissues of this same set of samples. This study provides a better understanding of the role of miRNAs in biological mechanisms related to feed efficiency in Nellore beef cattle.